Immunological events in acute measles influencing outcome. Issue 11 (November 1978) - Coovadia, H M; Wesley, A; Brain, P
Abstract : 77% of 30 children with measles who had severe lymphopenia (less than 2000/mm3; less than 2.0 x 10(9)/1) within 2 days of appearance of rash (group A) subsequently died or progressed to chronic chest disease. This was significantly worse than the outcome in 30 children with measles who had lymphocyte counts more than 2000/mm3 (more than 2.0 x 10(9)/1) (group B) of whom 67% recovered. In group A children the persistence of severe lymphopenia (caused by a reduction in T- and B-cells) for at least 15 days after onset of rash, remained a good predictive index of morbidity and mortality. Reversal of immunoparesis in group A was slower and incomplete 42 days from appearance of the rash in those who subsequently died or developed chronic chest disease compared with those who recovered. All patients who died failed to produce adequate measles antibodies. The therapeutic implications and immunopathological significance of these findings for chronic complications after acute measles are discussed.